Берегові радіолокаційні системи морського флоту як джерело впливу електромагнітних випромінювань на населення - Думанський, Ю.Д.; Томашевська, Л.А. (Актуальні проблеми транспортної медицини, 2005)
Electromagnetic situation in the areas of location and operation of coastal radars depends primarily of their technical characteristics and operation mode. The level of electromagnetic energy emitted by coastal radars in populated areas may range from 10 to 80 mkWt/cm2. In order to proved necessary sanitary hygienic conditions for the population dwelling in the vicinity of coastal radars hygienic standards should be differentiated with respect to the operation schedule. Changes of a body functions (physiological, immunological, biochemical and reproductive) caused by a long-termed electromagnetic exposures of 100, 500 and 2500 mkWt/cm2 were observed at the conditions of an experiment. Mathematical model of their biological effects detected, made it possible to establish the ineffective level of electromagnetic field at 10 mkWt/cm2 and recommend it as the maximum allowable level for living organisms.